CEO succession and the CEO's commitment to the status quo - Henning Behr; Kerstin Fehre (Business Research, 2019)
Chief executive officer (CEO) commitment to the status quo (CSQ) is expected to play an important role in any firm's strategic adaptation. CSQ is used often as an explanation for strategic change occurring after CEO succession: new CEOs are expected to reveal a lower CSQ than established CEOs. Although widely accepted in the literature, this relationship remains imputed but unobserved. We address this research gap and analyze whether new CEOs reveal lower CSQ than established CEOs. By analyzing the letters to the shareholders of German HDAX firms, we find empirical support for our hypothesis of a lower CSQ of newly appointed CEOs compared to established CEOs. However, our detailed analyses provide a differentiated picture. We find support for a lower CSQ of successors after a forced CEO turnover compared to successors after a voluntary turnover, which indicates an influence of the mandate for change on the CEO's CSQ. However, against the widespread assumption, we do not find support for a lower CSQ of outside successors compared to inside successors, which calls for deeper analyses of the insiderness of new CEOs. Further, our supplementary analyses propose a revised tenure effect: the widely assumed relationship of an increase in CSQ when CEO tenure increases might be driven mainly by the event of CEO succession and may not universally and continuously increase over time, pointing to a 'window of opportunity' to initiate strategic change shortly after the succession event. By analyzing the relationship between CEO succession and CEO CSQ, our results contribute to the CSQ literature and provide fruitful impulses for the CEO succession literature.
Keywords: 650; Commitment to the status quo (CSQ); CEO succession; CEO tenure; Computer-aided text analysis (CATA)